Efeitos da exposição ao ferro sobre a morte neuronal na substância negra de ratos durante o período neonatal - SANTOS, Bruno Lopes dos (2022)
Iron (Fe) is a chemical element directly involved in redox reactions due the possibility of donate and gain electrons in ferrous and ferric form, respectively. In overload states, the iron can generate free radicals derived from Haber-Weiss and Fenton reactions, finally resulting the generation of hydroxyl radical, the most pernicious free radical to the organism. In this context, it is known that the central nervous system is highly permeable to the iron in earlier stages of life, and the dopaminergic cells are more predisposed to the oxidative stress than another neurons. The aim of this work was to assess the effects of chronic iron administration in postnatal age over substantia nigra of rats. Lewis rats were used, distributed in 3 groups, accordingly the treatment duration: (1) from postnatal day 1 (P1) to P7, (2) P8 to P14 and (3) P1 to P14, and their controls (total of 6 groups). In treatment, it was administrated 30mg of Fe 2+/kg of body weight (ferrous sulfate solution) once a day, depending of the experimental group. Analysis of pyknotic profiles were made according to Macaya et al. (1994) and Marti et al. (1997), and number of marked tyrosine hydroxylase (TH) neurons by immunostaining were counted. The mean number of pyknotic profiles was higher in treated than control group only in P1-P7 duration, without differences between the other groups. The total number of pyknotic profiles was higher in treated group P1-P7. The number of TH positive dopaminergic neurons was lower in iron-exposed animals. These results suggest, even in earlier phase of exposition to an toxic agent (iron) in neonatal period, there is already some neuron loss in substantia nigra. It may result in future impairments, predisposing theparkinsonian syndrome development.